Lastnosti lesa iz rudnika Sitarjevec - Humar, Miha (Acta silvae et ligni, 2024)
The mining tradition in Litija, dating back to the Iron Age, involved the intensive use of wood in the mines, especially for support and protection. The Sitarjevec mine was reopened for tourism in 2017, and the central tunnel was opened in 2021. Wood remains a key material in the mines, although other materials have replaced it in the past. The wood used is subject to decay due to high humidity and fungi such as the mine fungus. This fungus can cause wood decomposition and is common in the humid environments of mines. The presence of fungi is important as it can affect visitors to the mine. The high relative humidity (96.6%) and constant temperature (10.1°C) in the mine create favourable conditions for fungal growth, although the relatively low temperature is not a limiting factor for wood decay. The high concentration of fungal spores in the mine is explained by the presence of fungi in the mine itself. In addition, we have observed that the wood contains a high level of inorganic contaminants and many crystals.
Keywords: bela hišna goba; crystals; decay; heavy metals; kristali; mining fungus; razkroj; spore; spores; težke kovine